Epigenetics in Familial Hypercholesterolaemia miRNA binding sites as regulators of genes involved in the lipid metabolism - Medeiros, A.M. (2020)
Familial hypercholesterolaemia is an autosomal dominant disorder of lipid metabolism characterized by elevated levels of LDL-C and increased cardiovascular risk. Although the disorder can be diagnosed based on established clinical criteria, only the genetic diagnosis confirms the clinical suspicion.